2012
DOI: 10.1371/journal.pone.0046831
|View full text |Cite
|
Sign up to set email alerts
|

Protective Antioxidant and Antiapoptotic Effects of ZnCl2 in Rat Pancreatic Islets Cultured in Low and High Glucose Concentrations

Abstract: Aim/HypothesisRat pancreatic islet cell apoptosis is minimal after prolonged culture in 10 mmol/l glucose (G10), largely increased in 5 mmol/l glucose (G5) and moderately increased in 30 mmol/l glucose (G30). This glucose-dependent asymmetric V-shaped profile is preceded by parallel changes in the mRNA levels of oxidative stress-response genes like Metallothionein 1a (Mt1a). In this study, we tested the effect of ZnCl2, a potent inducer of Mt1a, on apoptosis, mitochondrial oxidative stress and alterations of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 49 publications
3
26
0
5
Order By: Relevance
“…We (9,40) have previously shown that the glucose-induced changes in rat ␤-cell apoptosis are preceded by parallel changes in the oxidation of mt-roGFP1, a good indicator of mitochondrial thiol oxidation (32). Similar changes in mtroGFP1 fluorescence ratio were observed in the present study, with a large increase after culture at G5 vs. G10 and a small, significant increase after culture at G30 vs. G10 (Fig.…”
Section: Effects Of Ro On Glucose Regulation Of Gene Mrna Expression supporting
confidence: 86%
See 4 more Smart Citations
“…We (9,40) have previously shown that the glucose-induced changes in rat ␤-cell apoptosis are preceded by parallel changes in the oxidation of mt-roGFP1, a good indicator of mitochondrial thiol oxidation (32). Similar changes in mtroGFP1 fluorescence ratio were observed in the present study, with a large increase after culture at G5 vs. G10 and a small, significant increase after culture at G30 vs. G10 (Fig.…”
Section: Effects Of Ro On Glucose Regulation Of Gene Mrna Expression supporting
confidence: 86%
“…Histone-associated DNA fragments were measured in islet cell cytosolic extracts using the Cell Death Detection ELISA PLUS kit (Roche Diagnostics) exactly as described in (36). The percentage of apoptotic ␤-cells was determined on islet sections by TUNEL, using the In Situ Cell Death Detection Kit (Roche Diagnostics) followed by insulin immunostaining (9).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations